Gestión de ingresos y gastos y su relación con la gestión por objetivos del Hospital Regional de Loreto; Iquitos, año 2022 - Cahuaza Valderrama, Mercedes (2025)
The objective of this research was to identify how income and expense man agement is related to management by objectives at the Loreto Regional Hos pital in Iquitos, during the period 2022, with a quantitative research approach, non-experimental design and type of cross-sectional design with correlational scope; included 40 workers, both appointed and contracted, from the organic units of economics, strategic planning, treasury, budget, administration of the Regional Hospital of Loreto, the investigation concluded that The results show that the correlation between "Income and expense management " and "Man agement by objectives" is 0.656. This value indicates a moderate to strong positive correlation. Which suggests that, as income and expense manage ment improves, management by objectives also tends to improve, with respect to the bilateral significance is 0.000, indicating that the correlation is highly significant (p < 0 ,01). This suggests that it is very unlikely that this correlation occurred by chance, and that 80% of those surveyed consider that the revenue budget was executed correctly, although there is a notable division in satisfac tion with revenue management. -income (50% satisfied, 50% dissatisfied), 90% of respondents see alignment between physical goals and strategic ob jectives, 17.5% point out that there is no coherence between financial goals and the budget, suggesting areas for improvement in the planning.